2004
DOI: 10.1074/jbc.m310446200
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Androsterone (ADT) as a Cognate Substrate for Human Dehydroepiandrosterone Sulfotransferase (DHEA-ST) Important for Steroid Homeostasis

Abstract: In steroid biosynthesis, human dehydroepiandrosterone sulfotransferase (DHEA-ST) in the adrenals has been reported to catalyze the transfer of the sulfonate group from 3-phosphoadenosine-5-phosphosulfate to dehydroepiandrosterone (DHEA). DHEA and its sulfate play roles as steroid precursors; however, the role of the enzyme in the catabolism of androgens is poorly understood. Androsterone sulfate is clinically recognized as one of the major androgen metabolites found in urine. Here it is demonstrated that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…The structures of the M137I and M137W were determined by molecular replacement as implemented in CNS v1.1 (Brunger et al, 1998) using the crystal structure of human dehydroepiandrosterone sulfotransferase (Protein Data Bank code 1OV4) (Chang et al, 2004) as a search model. The M137I and M137W molecule was located in the asymmetry unit after rotation and translation function searches.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The structures of the M137I and M137W were determined by molecular replacement as implemented in CNS v1.1 (Brunger et al, 1998) using the crystal structure of human dehydroepiandrosterone sulfotransferase (Protein Data Bank code 1OV4) (Chang et al, 2004) as a search model. The M137I and M137W molecule was located in the asymmetry unit after rotation and translation function searches.…”
Section: Methodsmentioning
confidence: 99%
“…The catalysis and inhibition of DHEA and ADT by SULT2A1 have been reported to regulate the homeostasis and metabolism of these compounds and to maintain steroid levels (Chang et al, 2004). Previous studies have suggested that the onset of substrate inhibition is the formation of ternary dead-end complex (Duffel and Jakoby, 1981;Zhang et al, 1998).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The latter makes us conclude that potentiometry as a detection technique is more suitable than UV -Vis spectrophotometry for these GP derivatized 17-KS compounds, i.e., cationic ketosteroid pyridinium acetohydrazones. The underlying reason for not detecting the naturally occurring 17-KS concentrations in used human urine samples is that in such natural urine samples they are secreted mainly in their conjugated sulfated-and/or glucuronidated forms [7,48].…”
Section: Analysis Of Human Urine Biosamplesmentioning
confidence: 99%